KONSEP PENDIDIK DALAM ISLAM - Sudarto, Sudarto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
Educators are people who play an important role in educating the nation's children, while educators who speak what comes to our minds are adults who guide and give us something we don't know. The method used in this study is using qualitative methods, the characteristic of this approach lies in its hope of describing a case by capturing its interests and side effects, with the aim that the examination of the information used is scientifically enlightening. Information collection was carried out through library research techniques. From the results of this study it is known that in Islamic education, "educators" are often referred to as murobbi, mu'allim, mu'adddib, mudarris, and murshid. There are additional commitments and conditions that must be met by a teacher. Educators must also have several qualities that must be possessed as an educator. And there are still many parts of an educator that must be fulfilled.Keywords: Concept, Educator, Islam